A Time-Oscillating Hartree-Type Schrödinger Equation - Xu Chen (Abstract and Applied Analysis)
We consider the time-oscillating Hartree-type Schrödinger equation iut+Δu+θωtx-γ*u2u=0, where θ is a periodic function. For the mean value I(θ) of θ, we show that the solution uω converges to the solution of iUt+ΔU+Iθx-γ*U2U=0 for their local well-posedness and global well-posedness.